Perspektif Realisme tentang Kepentingan Nasional Rusia dalam Menyerang Ukraina - Annisa Rahma Dini; Bayu Setiawan; Yusuf Ali (Faculty of Social Science, Universitas Negeri Padang, 2023)
Conflict is unavoidable. Regardless of the nature of the conflict, war is the last alternative when the peace effort has failed to take. Russia's attack on Ukraine is the last stage in resolving the conflict due to the failure of peace negotiations between the two sides. This study aims to analyze the national interest of Russia in invading Ukraine through the perspective of realism. The method used in this research is a descriptive method with a qualitative approach. The data collection technique is secondary data through documentation or literature study. In this case, the researcher conducted previous research with the research topic studied from scientific articles in libraries and cyberspace. This study's results indicate an iceberg phenomenon in Russia's national interest in invading Ukrainian territory. Western expansion into the territory of Ukraine has created a security dilemma for Russia, so the war is used as momentum for Russia to achieve its national interests. Through the war, Russia played zero-sum to achieve its national interests, as a balance of power from Western powers, power expansion into the territory of Ukraine, and the power struggle. The armed conflict between the two countries is a challenge that must face by countries around the world, including Indonesia. In response to it, Indonesia used an independent-active principle based on Indonesia's national interests.